2018
DOI: 10.1051/matecconf/201815401055
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable-value stream mapping to evaluate sustainability performance: case study in an Indonesian furniture company

Abstract: Abstract. Lean manufacturing tools do not consider environmental and societal benefits. The conventional value stream mapping (VSM) methodology examines the economics of a manufacturing line, most of which are in regards to time (cycle time, lead time, change-out time, etc.). Incorporating the capability to capture environmental and societal performance visually through VSMs will increase its usefulness as a tool that can be used to assess manufacturing operations from a sustainability perspective. A number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…It was found to be impactful for waste elimination activities which facilitate in the visualization and analysis of information as well as the demonstration of value and non-value-added tasks in the mapping. Hartini et al (2018) pointed out that improvised LM tools like VSM can possibly possess a better visualization functionality of the triple bottom lines for sustainability performance assessment.…”
Section: Lean Manufacturingmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found to be impactful for waste elimination activities which facilitate in the visualization and analysis of information as well as the demonstration of value and non-value-added tasks in the mapping. Hartini et al (2018) pointed out that improvised LM tools like VSM can possibly possess a better visualization functionality of the triple bottom lines for sustainability performance assessment.…”
Section: Lean Manufacturingmentioning
confidence: 99%
“…From here, it is apparent that the VSM used in analyzing green and sustainable manufacturing has not been defined properly (Duflou et al, 2012). In general, the lack of research on this sustainable-oriented lean tool is still considered limited (Powell, Lundeby, Chabada, & Dreyer, 2017;Hartini, Ciptomulyono, Anityasari, Sriyanto, & & Pudjotomo, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, out of the wide range of lean tools available, value stream mapping (VSM) is deemed as one of the most significant ones [1], [5]. Hartini et al [28] indicated that VSM has the ability to visualize the triple bottom lines better in sustainability performance assessment. The tremendous support for VSM is an expected outcome due to its growing reputation, effectiveness and ease-of-use in improving sustainable performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…. (2010),Yang et al (2011),Duarte and Cruz-Machado (2013),Egilmez et al (2013),Chong et al (2016) Chemical consumptionFaulkner and Badurdeen (2014),Azapagic et al (2016),Cherrafi et al (2017),Hartini et al (2018), Jamil et al (2020) √ Water eutrophication Duarte and Cruz-Machado (2013), Prasara-A and Gheewala (2016) Air acidification Duarte and Cruz-Machado (2013), Mahmood et al (2015) Process water consumption Torres and Gati (2009), Lu et al (2011), Lu et al (2012), Brown et al (2014), Faulkner and Badurdeen (2014), Prasara-A and Gheewala (2016), Cherrafi et al (2017), Garza-Reyes et al (2018), Phuong and Guidat (2018), Hartini et al (2018) √ GHG emission Lu et al (2011), Deif (2011), Lu et al (2012), Faulkner and Badurdeen (2014), Mahmood et al (2015) Ratio of renewable energy consumed Lu et al (2011), Lu et al (2012), Urtiaga and Irabien (2013) Mass of restricted disposals Deif (2011), Lu et al (2011), Lu et al (2012), Faulkner and Badurdeen (2014) Noise level outside the factory Lu et al (2011), Lu et al (2012), Faulkner and Badurdeen (2014) Energy consumption Lu et al (2011), Lu et al (2012), Cherrafi et al (2017), Prashar (2017), Garza-Reyes et al (2018), Jamil et al (2020) √ Energy consumption on maintaining facility environment Lu et al (2011), Lu et al (2012), Egilmez et al (2013), Faulkner and Badurdeen (2014), Phuong and Guidat (2018) Energy consumption for transportation Lu et al (2011), Lu et al (2012), Song et al (2013), Faulkner and Badurdeen (2014), Jamil et al (2020) Eutrophication potential Mahmood et al (2015), Jamil et al (2020) Raw material usage Brown et al (2014), Faulkner and Badurdeen (2014), Garza-Reyes et al (2018), Jamil et al (2020)…”
mentioning
confidence: 99%